The first molecular phylogeny of the weevil subfamily Lixinae (Coleoptera: Curculionidae) casts doubts on the monophyly of its tribes - Volovnik, Semyon V.; Boldgiv, Bazartseren; Iderzorig, Badamnyambuu; Khobrakova, Larisa Ts.; Kolov, Sergey V.; Rudykh, Sergey G.; Zabaluev, Ilya A.; Grebennikov, Vasily V. (Zootaxa, 2021)
This paper targets the nearly cosmopolitan weevil subfamily Lixinae. A phylogenetic analysis of one mitochondrial and two nuclear DNA fragments obtained from 87 Lixinae and 49 outgroup terminals strongly supports the monophyly of the subfamily. The molytine tribe Mecysolobini is the likeliest sister group of Lixinae; adults of both taxa share the likely synapomorphic condition of the greatly shortened labial palpi. Phylogenetic relationships within the subfamily are poorly resolved. None of three Lixinae tribes is recovered as monophyletic. The subfamily’s oldest dichotomy is formed by a clade of two genera Rhabdorrhynchus plus Pachycerus sister to the rest of the subfamily. The genera Chromonotus, Larinus, Lixus, and Stephanocleonus are recovered as non-monophyletic. The genera Asproparthenis, Chromonotus, and Maximus form a strongly supported clade. The genus Eumecops is the likeliest sister to the clade formed by the genera Stephanocleonus plus Coniocleonus. The cleonine genus Scaphomorphus is a sister to a subset of externally most similar species of the genus Lixus; the same clade likely includes the genus Lixoglyptus not represented in the analysis. As an aside we provide a short summary of active flight in adult Cleonini.